Genetic variation within a dominant shrub structures green and brown community assemblages. Issue 2 (1st February 2014) - Crutsinger, Gregory M.; Rodriguez-Cabal, Mariano A.; Roddy, Adam B.; Peay, Kabir G.; Bastow, Justin L.; Kidder, Allison G.; Dawson, Todd E.; Fine, Paul V. A.; Rudgers, Jennifer A.
Abstract : Two rising challenges in ecology are understanding the linkages between above‐ and belowground components of terrestrial ecosystems and connecting genes to their ecological consequences. Here, we blend these emerging perspectives using a long‐term common‐garden experiment in a coastal dune ecosystem, whose dominant shrub species, Baccharis pilularis, exists as erect or prostrate architectural morphotypes. We explored variation in green (foliage‐based) and brown (detritus‐based) community assemblages, local ecosystem processes, and understory microclimate between the two morphs. Prostrate morphs supported more individuals, species, and different compositions of foliage arthropods, litter microarthropods, and soil bacteria than erect morphs. The magnitude of community compositional differences was maintained from crown to litter to soil. Despite showing strikingly similar responses, green and brown assemblages were associated with different underlying mechanisms. Differences in estimated shrub biomass best explained variation in the green assemblage, while understory abiotic conditions accounted for variation in the brown assemblage. Prostrate morphs produced more biomass and litter, which corresponded with their strong lateral growth in a windy environment. Compared to erect morphs, the denser canopy and thicker litter layer of prostrate morphs helped create more humid understory conditions. As a result, decomposition rates were higher under prostrate shrubs, despite prostrate litter being of poorer quality. Together, our results support the hypothesis that intraspecific genetic variation in primary producers is a key mediator of above‐ and belowground linkages, and that integrating the two perspectives can lead to new insights into how terrestrial communities are linked with ecosystem pools and processes.